Compassionate use of ruxolitinib in patients with SARS‐Cov‐2 infection not on mechanical ventilation: Short‐term effects on inflammation and ventilation. Issue 3 (27th January 2021) - Mortara, Andrea; Mazzetti, Simone; Margonato, Davide; Delfino, Pietro; Bersano, Chiara; Catagnano, Francesco; Lauriola, Marinella; Grosso, Paolo; Perseghin, Gianluca; Ippoliti, Giovanbattista
Abstract : Abstract: Ruxolitinib is an anti‐inflammatory drug that inhibits the Janus kinase‐signal transducer (JAK‐STAT) pathway on the surface of immune cells. The potential targeting of this pathway using JAK inhibitors is a promising approach in patients affected by coronavirus disease 2019 (COVID‐19). Ruxolitinib was provided as a compassionate use in patients consecutively admitted to our institution for severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) infection. Inclusion criteria were oxygen saturation less than or equal to 92%, signs of interstitial pneumonia, and no need of mechanical ventilation. Patients received 5 mg b.i.d. of ruxolitinib for 15 days, data were collected at baseline and on days 4, 7, and 15 during treatment. Two main targets were identified, C‐reactive protein (CRP) and PaO2 /FiO2 ratio. In the 31 patients who received ruxolitinib, symptoms improved (dyspnea scale) on day 7 in 25 of 31 patients (80.6%); CRP decreased progressively from baseline (79.1 ± 73.4 mg/dl) to day 15 (18.6 ± 33.2, p  = 0.022). In parallel with CRP, PO2/FiO2 ratio increased progressively during the 3 steps from 183 ± 95 to 361 ± 144 mmHg ( p  < 0.001). In those patients with a reduction of polymerase chain reaction less than or equal to 80%, delta increase of the PO2/FiO2 ratio was significantly more pronounced (129 ± 118 vs. 45 ± 35 mmHg, p  = 0.02). No adverse side effects were recorded during treatment. In patients hospitalized for COVID‐19, compassionate‐use of ruxolitinib determined a significant reduction of biomarkers of inflammation, which was associated with a more effective ventilation and reduced need for oxygen support. Data on ruxolitinib reinforces the hypothesis that targeting the hyperinflammation state, may be of prognostic benefit in patients with SARS‐CoV‐2 infection. Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? Some evidence suggest that patients affected by coronavirus disease 2019 (COVID‐19) present an exuberant inflammatory response represented by a massive production of type I interferons and different pro‐inflammatory cytokines. Nonetheless, as for the present, there are no proven therapeutic agents for COVID‐19, in particular anti‐inflammatory and antiviral, with a significant and reproducible positive clinical response. WHAT QUESTION DID THIS STUDY ADDRESS? Targeted therapeutic management of pro‐inflammatory pathways appears to be a promising strategy against COVID‐19, and ruxolitinib, due to its established broad and fast anti‐inflammatory effect, appears to be a promising candidate worthy of focused investigations in this field. WHAT DOES THIS STUDY ADD TO OUR KNOWLEDGE? Ruxolitinib rapidly reduces the systemic inflammation, which accompanies the disease, thereby improving respiratory function and the need of oxygen support. This effect may contribute to avoid progression of the disease and the use of invasive ventilation. HOW MIGHT THIS CHANGE CLINICAL PHARMACOLOGY OR TRANSLATIONAL SCIENCE? Data on ruxolitinib contributes the reinforcement of the hypothesis that it is crucial to counteract the early hyperinflammation state, particularly of the lungs, induced by COVID‐19 infection.